90.1k views
5 votes
What is the solution to the equation 4x + 2(x − 2) = 4x + x − 12?

−8
−1
1
8
My last question for now thanks everyone for the help
i think the answer is -8 if anyone could check for me that would help

User Aliquis
by
4.9k points

2 Answers

6 votes

Answer:

-8 is the correct answer

Explanation:

I got it right on the test.

User Stephano
by
5.2k points
6 votes
Equation: 4x + 2(x - 2) = 4x + x - 12



Solve:
4x + 2(x - 2) = 4x + x - 12

4x + (2)(x) + (2)(- 2) = 4x + x + - 12 (Distribute)

4x + 2x + - 4 = 4x + x + - 12

(4x + 2x) + (- 4) = (4x + x) + (- 12)

Combine Like Terms:
6x + - 4 = 5x + - 12

6x - 4 = 5x - 12



Subtract 5x from both sides:
6x - 4 - 5x = 5x - 12 - 5x

x - 4 = - 12


Add 4 to both sides:
x - 4 + 4 = - 12 + 4

x = - 8


Answer: x = - 8





Hope that helps!!!! ( x = - 8, Letter Choice (A).
User Aviv Ben Shabat
by
6.0k points